1998
DOI: 10.1128/aac.42.9.2197
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mode of Action of the Antifungal β-Amino Acid BAY 10-8888

Abstract: BAY 10-8888 is a cyclic β-amino acid that is related to cispentacin and that has antifungal activity. Candida albicans cells accumulated BAY 10-8888 intracellularly to a concentration about 200 that in the medium when grown in media with a variety of nitrogen sources. In complex growth medium, BAY 10-8888 transport activity was markedly reduced and was paralleled by a decrease in its antifungal activity. Uptake of BAY 10-8888 was mediated by an H+-coupled amino acid transporter with specificity for branched-ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 25 publications
0
25
0
Order By: Relevance
“…While inhibitors of the C. albicans leucine biosynthetic pathway alone would have little utility in vivo since leucine auxotrophs are virulent (Kirsch & Whitney, 1991; Noble & Johnson, 2005), since the toxic effects in ilv2 Δ mutants are likely due to isoleucine and valine starvation, inhibitors of other isoleucine and valine biosynthetic enzymes would likely also be effective. Furthermore, given that isoleucine starvation is also fungicidal and the ilv1 Δ mutant is somewhat attenuated in virulence in C. albicans , any inhibitor targeting an isoleucine-biosynthetic enzyme should have a clinically beneficial interaction with any of the various isoleucyl tRNA synthetase inhibitors currently available with antifungal activity, such as the antibacterial agent mupirocin (Nicholas et al , 1999), or the anticandidal drug BAY 10-8888 (PLD-118) (Ziegelbauer, 1998; Ziegelbauer et al , 1998). Finally, since the growth rate of ilv2 Δ mutants was reduced compared with the wild-type even in the presence of abundant levels of isoleucine and valine, Ilv2p inhibition may not require complete absence of isoleucine and valine from the environment to have a therapeutic benefit.…”
Section: Discussionmentioning
confidence: 99%
“…While inhibitors of the C. albicans leucine biosynthetic pathway alone would have little utility in vivo since leucine auxotrophs are virulent (Kirsch & Whitney, 1991; Noble & Johnson, 2005), since the toxic effects in ilv2 Δ mutants are likely due to isoleucine and valine starvation, inhibitors of other isoleucine and valine biosynthetic enzymes would likely also be effective. Furthermore, given that isoleucine starvation is also fungicidal and the ilv1 Δ mutant is somewhat attenuated in virulence in C. albicans , any inhibitor targeting an isoleucine-biosynthetic enzyme should have a clinically beneficial interaction with any of the various isoleucyl tRNA synthetase inhibitors currently available with antifungal activity, such as the antibacterial agent mupirocin (Nicholas et al , 1999), or the anticandidal drug BAY 10-8888 (PLD-118) (Ziegelbauer, 1998; Ziegelbauer et al , 1998). Finally, since the growth rate of ilv2 Δ mutants was reduced compared with the wild-type even in the presence of abundant levels of isoleucine and valine, Ilv2p inhibition may not require complete absence of isoleucine and valine from the environment to have a therapeutic benefit.…”
Section: Discussionmentioning
confidence: 99%
“…They serve as artificial substrate and get accumulated in fungal cells by amino acid permease. Once inside the cell 44 and 45 also inhibit fungal protein biosynthesis by inhibiting isoleucyl-tRNA synthase [110][111][112].…”
Section: Isoleucyl-trna Synthasementioning
confidence: 99%
“…The growth inhibitory effects of the agent were reversed by intracellular L-isoleucine. PLD-118 inhibiteed isoleucyl in a concentration-dependent manner, with a K i of 1 mM obtained, suggesting that the interaction of the agent with its substrate is not very specific (13,20). Further analysis of the mechanism of action of PLD-118 revealed that accumulation of the agent into selected C. albicans mutants was reduced while isoleucyl-tRNA synthetase activity was increased.…”
Section: Introductionmentioning
confidence: 99%
“…1). Cyclic β-amino acids are one class of potent antifungals that appear to a have a dual mode of action: inhibition of protein synthesis after concentrative uptake and interference with self-regulatory mechanisms of amino acid metabolism (12,13). Cispentacin is a naturally occurring cyclic β-amino acid with potent in vitro and in vivo anti-Candida activity including inhibitory activity against C. albicans, Candida krusei and Candida tropicalis (MIC range for Candida spp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation